2017
DOI: 10.20960/nh.882
|View full text |Cite
|
Sign up to set email alerts
|

Effects unrelated to anti-inflammation of lipid emulsions containing fish oil in parenteral nutrition for adult patients

Abstract: Mateu-de-Antonio J, Florit-Sureda M. Effects unrelated to anti-infl ammation of lipid emulsions containing fi sh oil in parenteral nutrition for adult patients. Nutr Hosp 2017;34:193-203 ResumenSe han publicado varias revisiones y metaanálisis sobre la modulación de las respuestas infl amatorias e inmunológicas por la administración de ácidos grasos poliinsaturados (AGPI) omega-3. Sin embargo, los AGPI omega-3 ejercen otras acciones no directamente relacionadas con estas respuestas. El objetivo de este tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The detailed differences of the pathomechanisms that underlie liver damage in both PN-dependent paediatric and adult patients are beyond the scope of this paper. More information is available in some excellent recent reviews [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed differences of the pathomechanisms that underlie liver damage in both PN-dependent paediatric and adult patients are beyond the scope of this paper. More information is available in some excellent recent reviews [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 24 27 Numerous adult studies have shown that fish oil containing lipid emulsion has a positive effect on liver enzyme tests and prevention of PN-associated liver disease in surgical or critically ill patients. 28 30 Three studies showed a 15% to 25% faster plasma lipid clearance or 25% to 45% shorter half-life of experimental fish oil containing lipid emulsion, even with different fish oil content. 31 33 Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature the etiology of PN-associated cholestasis is multifactorial, with causes including prematurity, lack of enteral nutrition, sepsis, and factors relevant to the duration and composition of the PN [15][16][17][18]. Numerous adult studies have revealed that fish oil containing lipid emulsion has a positive effect on liver enzyme tests and prevention of PN-associated liver disease in surgical or critically ill patients [19][20][21]. Three studies resulted in a 15-25% faster plasma lipid clearance or 25-45% shorter half-life of the experimental fish oil containing lipid emulsion, even with different fish oil content [22][23][24].…”
Section: Discussionmentioning
confidence: 99%